Voltage Control in Low Voltage Distribution Networks with High Penetration Photovoltaic System - Leon, J. S. [UNESP]; Padilha-Feltrin, A. [UNESP]; Melo, J. D.; Sguarezi Filho, Alfeu J.; IEEE (Ieee, 2017)
Photovoltaic generators can provide several benefits for distribution networks, such as power loss reduction, and improvements in voltage level. However, high penetration of these generators can cause voltage rise problems in the distribution network. In this way, voltage control strategies are necessary so that the voltage levels are within the range of operation for any load and generation conditions. This paper proposes a global voltage control in low voltage distribution networks in order to maintain the voltage in the allowable operating range. For that it is done the minimum reduction of active power injection of the photovoltaic generators (these are implemented with variable power factor). The power reduction is determined with the model of nonlinear programming. The proposed voltage control was compared to voltage control using linear programming to show the benefits of solving the voltage rise problem using a non-linear strategy.
Keywords: Low voltage distribution networks; voltage rise problems; voltage control; photovoltaic generation